Analisis Pertumbuhan Laba Terhadap Nilai Perusahaan Studi Kasus Pada PT INDOFOOD SUKSES MAKMUR, Tbk dan PT MAYORA INDAH, Tbk - Sutarti, Sutarti; Sutisna, Bambang (Jurnal Ilmiah Ranggagading (JIR), 2012)
The objective of financial management is to maximize shareholdersâ welth by increasing firm value, that is intrinsic and market value of the company. The objective can be achieved by increasing profit. The increase of profit every year means the company has profit growth. By profit growth, the companyâs intrinsic and market value will have increase as well. Intrinsic value is fair value of stock based on the companyâs financial performance, while stock market value is stock market prevailing in the market. The purpose of this study is to determine the effect of profit growth, as measured by net profit growth per year towards its intrinsic value as measured by earning multiplier and market value as measured by stock market price. This research was conducted from 2006 until 2010, by taking sample of two companies, namely PT Indofood Sukses Malmur, Tbk. and PT Mayora Indah, Tbk. Based on the analysis, the profit growth at PT Indofood Sukses Makmur, Tbk. could increase impact on intrinsic value and market value of the company. It was shown in the year 2009 â 2010. But in the year 2006 â2007, 2007 â 2008, and 2008 â2009 the change of profit growth was not be able to increase intrinsic and market value of the company. The profit growth at PT Mayora Indah, Tbk. could increase intrinsic and market value of the company. It was shown in the year 2006 â 2007. In the year 2008 â 2009 the profitgrowth was withheld and return on equity increased, resulting impact on intrinsic and market value of the company. It was shown in the year 2009 â 2010 as well. But inthe year 2007 â 2008 the profit growth was notable to increase intrinsic and market value of the company. The result is the profit growth at PT Mayora Indah, Tbk. has impact on intrinsic and market value better than the profit growth at PT Indofood Sukses Makmur, Tbk. has it.